Appraisal Theory: Can It Be Applied to Visual Images in Isolation to the Text? - Alzahrani, Bashayir; Alhuthali, Mohammed (European Scientific Journal, ESJ, 2024)
The role of women in Saudi society is changing, but even the process of reform is subject to multiple interpretations. This makes the role of resemiosis when interpreting visual media particularly important, perhaps more than a direct focus on the semiotic modes adopted. Appraisal Theory captures this judgement process in terms of emotions experience by the reader/viewer and how the wider context such as the full news article, or even just the headline, forms a part of this process. This argues that in contested situations resemiosis is a critical part of the process and sometimes the apparent interpretation of a single image (intersemiosis) can be different to the interpretation of the whole. In these cases, it is not just that different semiotic modes carry different meanings but that a focus on one in isolation can be misleading as to the overall intent.